Posted by
**Jasmine202005** on
.

How do i solve inequalitites with three variables. I still can't figure it outplease help.

x+y=1

y-z=-3

2x+3y+z=1

THE ANSWERS ARE X=3,Y=-2,Z=1

i KNOW THE ANSWERS I JUST DON'T KNOW HOW THE BOOK GOT THE ANSWERS . i 'VE TRIED MANY DIFFERENT WAYS AND I STILL DONT' UNDERSTAND IT PLEASE EXPLAIN IT.

i KNOW THAT I HAVE TO ADD EQUATION 2 AND THREE TO GET THE FOLLOWING

2X+3Y+Z=1

Y-Z=-3

IN ORDER TO GET

2X+4Y=-2

THEN I DON'T KNOW FROM HERE

There a couple ways to solve this. You have

x+y = 1

y-z =-3

2x+3y+z= 1

You could first show

x=1-y and z=y+3 and substitute them into the 3rd equation to get

2(1-y)+3y+y+3=1 and solve for y to get

2-2y+3y+y+3=1

5+2y=1 so 2y=-4 and y=-2

then put this into the first two equations to solve for x and z.